Postoperative factors associated with psychological well-being of living kidney donors: results of a retrospective and qualitative study - Galani, Vasiliki; Mazzola, Viridiana; Prada, Paco; Bondolfi, Guido (Frontiers in Psychology, 2024)
Kidney transplantation from a living donor is the treatment of choice for end-stage kidney disease.Psychological implications of living kidney donation are of great importance, both during preliminary psychiatric assessment and post-donation follow-up. The identification of risk factors worsening the psychological well-being of living kidney donors (LKDs), before and after donation, remains challenging in terms of research. At the University Hospitals of Geneva (HUG), our clinical observations and practice compelled us to establish post-donation follow-ups for LKDs at six months and one year. Pre-and post-donation sociodemographic, physical, psychological, and psychiatric data was collected from the medical records of LKDs. A qualitative and retrospective analysis of this data highlighted the impact of postoperative factors, such as pain, fatigue, recipient-donor relationship, and fulfilment of donors' expectations, on the post-donation psychological well-being of LKDs. With regard to these findings, regular post-donation follow-ups, optimal care of postoperative pain and fatigue, as well as a solid therapeutic alliance with LKDs remain key points for clinicians involved in the dynamic process of living kidney donation.